If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + 3b + c = 4 Solving 9a + 3b + c = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 9a + 3b + -3b + c = 4 + -3b Combine like terms: 3b + -3b = 0 9a + 0 + c = 4 + -3b 9a + c = 4 + -3b Add '-1c' to each side of the equation. 9a + c + -1c = 4 + -3b + -1c Combine like terms: c + -1c = 0 9a + 0 = 4 + -3b + -1c 9a = 4 + -3b + -1c Divide each side by '9'. a = 0.4444444444 + -0.3333333333b + -0.1111111111c Simplifying a = 0.4444444444 + -0.3333333333b + -0.1111111111c
| 12-10x=122-45x | | 8y+7=-6y+2 | | 10+4x=3(7x-4)+5x | | -21p^2-24p=12 | | (-x^5)(-x)= | | 10x+2=-2+4 | | 2kx*2kx=0 | | (3x+9)+(6x+7)= | | 5x+10=4x+15 | | 6x+10y+11=0 | | x^2+2kx-7=0 | | -10p+3(8+8n)=-6(n-4) | | 137-5x=-58-8x | | 5x+9=39-7x | | 3y(5y+9)=0 | | 63-6x=9+18 | | 5x-3(x-10)=100-2(3x+5) | | 2(g+6)=24 | | .83=-.4b+.33b | | 5(g+6)=24 | | 3(x^2+4x+4)=0 | | n+8m=d | | 30n=-5 | | x=42*7 | | 2x(x-1)=5(x+3) | | 2x^3-11x^2+22x-15=0 | | 5x+31=14x-92 | | 945000+x=10x | | X^3-2x^2+3x+4=0 | | 5x-3(x-2)=30-3(x+3) | | 0.2x^2-80x+2500=0 | | 2t=34 |